Toward a better understanding of the experience of patients with moderate penetrance breast cancer gene pathogenic/likely pathogenic variants: A focus on ATM and CHEK2. Issue 4 (4th March 2022) - McCormick, Shelley; Hicks, Stephanie; Wooters, Mackenzie; Grant, Carly
Abstract: This study explored the experiences of patients with pathogenic or likely pathogenic variants in the moderate penetrance breast cancer genes, ATM and CHEK2 . There were 139 eligible female patients who received genetic counseling at the Massachusetts General Hospital Center for Cancer Risk Assessment (MGH CCRA) from 2014 to 2018. They were sent surveys assessing their understanding of the clinical significance of their genetic test results, adherence to medical management recommendations, dissemination of genetic test results to relatives, and informational resource needs. In total, 66 surveys were returned with a response rate of 47.5%. Most participants reported understanding the clinical implications of their genetic test results and adhering to medical management recommendations. Although 20.3% found it upsetting, nearly all participants shared their genetic test results with relatives. When asked about resource needs, 54.5% reported seeking out additional resources. Our ATM / CHEK2 sample appears to have a good understanding of the personal and familial implications of their genetic test results but may benefit from additional resources. It is unclear whether similar results would be found in patients who do not receive genetic counseling from a board‐certified genetic counselor, and this should be examined. This study is one of the first to assess the experiences and needs of the moderate risk population.